2012
DOI: 10.1088/0957-0233/23/9/094001
|View full text |Cite
|
Sign up to set email alerts
|

Length and refractive index measurement by Fourier transform interferometry and frequency comb spectroscopy

Abstract: In this paper we describe the progress we have made in our simultaneous length measurement and the femtosecond comb interferometric spectroscopy in a conventional arrangement with a moving mirror. Scanning and detection over an interval longer than the distance between two consecutive pulses of the frequency comb allow for a spectral resolution of the individual frequency modes of the comb. Precise knowledge of comb mode frequency leads to a precise estimation of the spectral characteristics of inspected pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 38 publications
0
40
0
Order By: Relevance
“…The spectral comb structure starts to be visible when an interferogram containing several bursts is acquired [5]. However, unless the interferogram is sampled correctly, the spectral resolution is limited to the nominal resolution of the FTS and retrieving the power of comb modes requires interpolation between the FTS sampling points [6]. Recently, we have shown that the power of the comb modes can be precisely measured using single-burst interferograms with the length matched to c/frep [7].…”
Section: Introductionmentioning
confidence: 99%
“…The spectral comb structure starts to be visible when an interferogram containing several bursts is acquired [5]. However, unless the interferogram is sampled correctly, the spectral resolution is limited to the nominal resolution of the FTS and retrieving the power of comb modes requires interpolation between the FTS sampling points [6]. Recently, we have shown that the power of the comb modes can be precisely measured using single-burst interferograms with the length matched to c/frep [7].…”
Section: Introductionmentioning
confidence: 99%
“…Also, direct application in gauge block measurement has been explored (see Chapter 4), as well as simultaneous measurement of the thickness and refractive index (and dispersion) of flat samples [51].…”
Section: Modern and Future Laser Frequency Standardsmentioning
confidence: 99%
“…When using a frequency comb [16,17] (see also Section 2.9.6), the uncertainty in the vacuum wavelength will be negligible compared to other factors. Formally, it sounds very good that the calibration is directly traceable to a primary standard, but for the uncertainty, the other factors mentioned are more important.…”
Section: Vacuum Wavelengthmentioning
confidence: 99%
“…Using a frequency comb (see Section 2.9.6) opens up some interesting new possibilities [16,17], where a beam full of well-defined frequencies can be used both as a white light source that defines an absolute position in space, and as an accurate distance and/or displacement measurement that can be combined to an absolute gauge block length in single-and double-sided set-ups. Double-sided gauge block interferometer [28].…”
Section: Alternative Approachesmentioning
confidence: 99%